(untitled) (Gestión y Gerencia, 2023)
Organizations that provide management advisory and consulting services are eager to generate value in their business models, and therefore, in the products and services they offer to their clientele. Therefore, to achieve this goal, Digital Transformation (DT) is seen as an opportunity to increase its chances of success in order to be more competitive, as well as to achieve a much more privileged level of positioning in the market arena. Therefore, this article is aimed not only at knowing some conceptual generalities about the DT process, but also places emphasis on addressing some proposed models that could easily permeate the organizations under study, depending on whether It’s adequate adaptation to the realities and contexts of consulting companies allows the generation of value as a differentiating element in the execution of its services. Likewise, a comparison of all the models studied was carried out, with a view to verifying the existence of structural similarities in them, concluding that any of them can be suitable for implementation in organizations, as long as this process adapts to the specific needs and features of each company.